Improving the Access of Cardiac Magnetic Resonance in Low-Middle Income Countries to Improve Cardiac Care: Rapid CMR - Menacho Medina, Katia Devorha (2021)
Non-communicable diseases– cancer and cardiovascular disease - are the leading causes of death in high-income countries (HICs). Cardiovascular disease, however, is increasing in Low-Middle Income Countries (LMICs) and is the emergent primary cause of mortality. Part of the reason is suboptimal therapies– from primary prevention to more advanced tertiary care. Not only are advanced therapies scarce but advanced diagnostic tests which apply to them are not fully available, and so diagnoses could be inaccurate and treatments poorly targeted. Within the portfolio and hierarchy of cardiovascular diagnostic testing, Cardiac Magnetic Resonance (CMR) is a crucial diagnostic imaging test that redefines diagnosis and enables targeted therapies, but is expensive with inadequate training and poor availability in LMICs countries. I demonstrated that CMR could be made fast, easy, and cheap – sufficient for delivery in five LMICs countries in three continents. To achieve this, I developed an abbreviated CMR protocol, focused on the core of CMR - volumes, function, and scar imaging (with selected additions like iron quantification), and by embedding the technical quality protocol within clinical care, training, and mentoring, so it proved to have diagnostic utility and change management, as well being a self-sustaining and essential service. I also used CMR as a research method in LMICs specifically to complement research in areas of a specific need to those countries, exploiting opportunities that were previously unavailable, with one chapter dedicated to evaluating early cardiovascular involvement in treated and non-treated people living with HIV in Peru, and a second chapter of the potential utility of CMR for screening cardiotoxicity and its comparison in precision with other cardiac imaging modalities in the UK, potentially extending the role of rapid CMR in HICs. Unlike traditional PhDs in medicine, my research involved technology adaptation, transfer, and collaboration. The project was multi-layered with political, social, educational, training, and partnership aspects, along with more traditional aspects such as clinical effectiveness and cost-effectiveness analysis. I showed the use of advanced cardiac imaging in LMICs by breaking down barriers, demonstrating that Rapid CMR can be possible in new clinical environments where much need exists.